Role of prolactin in the regulation of cytosolic NADP isocitrate dehydrogenase in the liver of the male rat - Zirulnik, Fanny (2003)
The activity of cytosolic NADP-linked isocitrate dehydrogenase (ICDH) in rat liver was determined. The administration of 2-bromo-α-ergocryptine (CB-154) to male rats produced a significant increase of the enzyme activity and a decrease of serum prolactin (PRL) levels in relation to control animals. Male rats 21 days after castration had lower levels of serum prolactin and higher activity of the enzyme than controls. Injection of PRL to castrated male rats lowered the enzymatic activity to control values. In intact rats injected with prolactin, the activity of the enzyme also decreased. Female rats were separated into the following groups: (a) virgins; (b) rats on day 15 of lactation; (c) ovariectomized rats. The enzymatic activity was similar in the different groups, but significantly higher than in male rats. However, serum PRL was significantly increased in 15 days lactating rats and decreased in ovariectomized ones in relation to virgins. We conclude that PRL regulates hepatic ICDH activity in male, but not in female rats. Incubation of isolated hepatocytes from intact or castrated male rats maintained the difference in ICDH activity observed in vivo, while there were no differences in ICDH activity in non-parenchymal cells. Addition of PRL, CB-154, androgens or antiandrogens to isolated hepatocytes from intact and castrated rat, had no effect on the ICDH activity, suggesting that the effect of PRL is exerted at the transcriptional level.